Addressing challenges in the practice of critical literacy in EFL classrooms: A new framework - Novianti, Nita; Thomas, Angela; To, Vinh (Universitas Pendidikan Indonesia, 2020)
The practice of critical literacy in EFL contexts answers the need for EFL pedagogy that considers the complex social and political dimensions of foreign language learning. Many teachers are still discouraged from practicing critical literacy due to the many challenges they encounter. In this paper, we outline a practical framework that can help teachers navigate the complexity of practicing critical literacy in EFL contexts. The framework consists of four resources of critical literacy practice, namely curriculum and standards, students’ experiences and background, local social issues, and text selection. The classroom activities include text analysis and critique, bridging the word and the world, and social action. Particular issues in EFL pedagogy are addressed with implications for the practice of critical literacy.